2013
DOI: 10.1186/1471-2407-13-196
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of colon cancer associated transcript1 (CCAT1) along the colonic adenoma-carcinoma sequence

Abstract: BackgroundThe transition from normal epithelium to adenoma and, to invasive carcinoma in the human colon is associated with acquired molecular events taking 5-10 years for malignant transformation. We discovered CCAT1, a non-coding RNA over-expressed in colon cancer (CC), but not in normal tissues, thereby making it a potential disease-specific biomarker. We aimed to define and validate CCAT1 as a CC-specific biomarker, and to study CCAT1 expression across the adenoma-carcinoma sequence of CC tumorigenesis.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 38 publications
1
92
0
Order By: Relevance
“…CCAT1 is markedly overexpressed in CRC 84 and is also upregulated in precancerous tissues, including benign inflammatory colonic tissues and adenomatous polyps. 85 CCAT1 can be detected in CRC tissue and in the blood and stool samples of CRC patients. 86 Thus a CCAT1-based blood/stool assay may be explored for the screening and early detection of CRC.…”
Section: Tumor Diagnosismentioning
confidence: 99%
“…CCAT1 is markedly overexpressed in CRC 84 and is also upregulated in precancerous tissues, including benign inflammatory colonic tissues and adenomatous polyps. 85 CCAT1 can be detected in CRC tissue and in the blood and stool samples of CRC patients. 86 Thus a CCAT1-based blood/stool assay may be explored for the screening and early detection of CRC.…”
Section: Tumor Diagnosismentioning
confidence: 99%
“…3,4 Colon cancer-associated transcript 1 (CCAT1), a ~2-kb lncRNA located at chromosome 8q24.21, is first found to be upregulated in colon cancer. 5 Recently, some reports have found that CCAT1 is involved in tumor progression and tumorigenesis in various types of cancers including colon cancer, 6 gastric cancer, 7 and colorectal cancer. 8 The competitive endogenous RNA (ceRNA) mechanism for CCAT1 and microRNAs involving in tumor progression has been reported in some studies, for example, Zhou et al 9 reported the lncRNA CCAT1/miR-490 axis regulated gastric cancer cell migration by targeting hnRNPA1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aberrantly expressed lncRNAs have been found related with CRC. As examples, lncRNAs such as CCAT1 [24][25], CCAT2 [26], HOTAIR [27] and MALAT1 [28] are increased in CRC tissues compared to NATs and have been identified as oncogenes. The lncRNAs can regulate the expression of their target genes, activate some signaling pathways, and promote cell proliferation, metastasis, and tumor recurrence [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%